Genetic Variability and Correlation Coefficients of Major Traits in Cold Tolerance Rice (Oriza sativa L.) Under Mountain Environment of Nepal - Ghimire, Netra Hari; Mahat, Paras Mani (International Journal of Applied Sciences and Biotechnology, 2019)
This study was conducted at Agricultural Research Station (ARS), Vijayanagar, Jumla Nepal comprising fifteen genotypes of cold tolerance rice during regular rice growing season of high hill in 2015 in RCBD (Randomized Complete Block Design) with three replications to observe genetic variability, correlation, heritability, genetic advance and clustering of genotypes in relation to yield and yield associated traits and selection and advancement of early maturing, high yielding, disease resistant, and cold tolerance genotypes for high mountain area. Analysis of variance revealed that all characters except number of panicle per hill were significantly different indicating presence of variation in genetic constituents. Phenotypic coefficient of variance (PCV) was higher than genotypic coefficient of variance (GCV) for all the corresponding traits under study indicating environmental influence for the expression of the traits. Higher PCV and GCV value were obtained in grain yield (Yld), number of grain per panicle (NGPP) and number of panicle per hill (NPPH). Higher heritability coupled with higher genetic advance (GA) was obtained in NGPP, NPPH and Yld, high heritability and medium GA was obtained in thousand grains wt (TGW), plant height (Pht) and panicle length (PL) indicating additive gene action indicating direct selection may be a tool for varietal development. Positive and significant correlation was obtained between all characters except DM and Pht, PL and PHT and TGW and PPH. Total three clusters were obtained in eighty percent euclidean similarity clustering indicating genetic closeness/distances among the genotypes. Culture 1 carries the superior five genotypes including NR-10638-B-B-4 and NR-10695-B-B-B. Int. J. Appl. Sci. Biotechnol. Vol 7(4): 445-452